Coherence of achromatic, primary and basic classes of colour categories. (October 2020) - Mylonas, Dimitris; Griffin, Lewis D.
Highlights: Subsets of colour categories should form a coherent class. Achromatic and Basic colour categories form coherent classes. Primary colour categories do not form a coherent class. Abstract: A range of explanations have been advanced for the systems of colour names found in different languages. Some explanations give special, fundamental status to a subset of colour categories. We argue that a subset of colour categories, if fundamental, will be coherent - meaning that a non-trivial criterion distinguishes them from the other colour categories. We test the coherence of subsets of achromatic (white, black and grey), primary (white, black, red, green, yellow, blue) and basic (primaries plus brown, orange, purple, pink and grey) colour categories in English. Criteria for defining colour categories were expressed in terms of behavioural, linguistic and geometric features derived from colour naming and linguistic usage data; and were discovered using machine learning methods. We find that achromatic and basic colour categories are coherent subsets but not primaries. These results support claims that the basic colour categories have special status, and undermine claims about the fundamental role of primaries in colour naming systems.